2018
DOI: 10.1002/bkcs.11653
|View full text |Cite
|
Sign up to set email alerts
|

Determining Collision Cross‐Sections of Aromatic Compounds in Crude Oil by Using Aromatic Compound Mixture as Calibration Standard

Abstract: Collisional cross section (CCS) values of a set of aromatic compounds were determined and the compounds were evaluated as standards for calibration and standardization. External calibration with poly-DL-alanine and internal and external calibration with the aromatic compounds were performed using the ion mobility mass spectra obtained from crude oils. The results showed that the external calibration method using the set of aromatic compounds is both accurate and easy to implement. The improved accuracy obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…The separation of isomers using IM-MS has been reported in prior literature (Lalli et al, 2015). In addition, the CCS measurement can be performed for the structural characterization of compounds in a complex mixture (Ahmed et al, 2011;Becker et al, 2008;Santos et al, 2015) Experimental details for accurate CCS measurements have also been described (Gabelica et al, 2019;Lim, Davidson, et al, 2019;Lim, Park, et al, 2019). Fernandez-Lima et al (2009) and Leyva et al (2020) showed that complementary FT-ICR MS and IM-MS analyses of crude oils could resolve the compositional Kostyukevich, Kononikhin, Popov, Kharybin, et al, 2013.…”
Section: Orthogonal Approaches For Structural Identificationmentioning
confidence: 99%
“…The separation of isomers using IM-MS has been reported in prior literature (Lalli et al, 2015). In addition, the CCS measurement can be performed for the structural characterization of compounds in a complex mixture (Ahmed et al, 2011;Becker et al, 2008;Santos et al, 2015) Experimental details for accurate CCS measurements have also been described (Gabelica et al, 2019;Lim, Davidson, et al, 2019;Lim, Park, et al, 2019). Fernandez-Lima et al (2009) and Leyva et al (2020) showed that complementary FT-ICR MS and IM-MS analyses of crude oils could resolve the compositional Kostyukevich, Kononikhin, Popov, Kharybin, et al, 2013.…”
Section: Orthogonal Approaches For Structural Identificationmentioning
confidence: 99%
“…To have a snapshot of the global structure of laboratory tholins sample, we added two wellknown families from our experimental measurements: tetra-alkylammonium ions (TAA), which were used as reference CCS, and polyglycine. In addition, polycyclic aromatic hydrocarbon was added from precedent measurements (PAH) (Campuzano et al, 2012;Lim et al, 2018). All these families are listed in the table S2 and a comparison is given between experimental measurements and database CCS in order to validate our results.…”
Section: Ims-ms Experimentsmentioning
confidence: 99%
“…Consequently, ion mobility drift times correlate strongly with molecular weight. Great progress has been achieved at multiple laboratories in the recent decade on the applications of IM-MS for petroleum characterization. Fernandez-Lima et al combined IM-MS with FT-ICR MS to analyze several crude oils. They showed that high molecular weight components of petroleum crude resulted from noncovalent aggregation.…”
Section: Ion Mobility Mass Spectrometrymentioning
confidence: 99%
“…Farenc et al proposed a simple indicator to estimate the isomeric content of highly complex mixtures, based on the full width at half-maximum of the extracted ion mobility peak. Lim and co-workers , determined collisional cross sections of aromatic compounds in crude oil and further developed molecular dynamics simulations to improve the theoretical prediction for collisional cross sections of aromatic compounds with long alkyl chains in crude oils.…”
Section: Ion Mobility Mass Spectrometrymentioning
confidence: 99%